Experimental Study on Temperature Distribution Characteristics Under Coordinated Ventilation in Underground Interconnected Tunnels - Houlin Ying; Zhisheng Xu; Zihan Yu; Yaolong Yin; Weibing Jiao (Fire)
Underground interconnected tunnels typically have a large curvature and multiple branching structures, which pose a higher fire risk than traditional single-tube tunnels. In this paper, experiments were performed on a reduced-scale tunnel to study the characteristics of temperature distribution and smoke propagation under coordinated ventilation. A total of 318 experimental cases were conducted, systematically varying fire location, ventilation scheme, and fire power. The results show that an increased heat release rate (HRR) significantly elevates both the maximum temperature (<semantics>ΔTmax</semantics>) and smoke spread range. The influence of ventilation on <semantics>ΔTmax</semantics> and smoke spread varies depending on fire locations. When fire occurs at the intersection of two tunnel central axes, increasing the velocity in either the branch tunnel (v1) or main tunnel (v2) reduces <semantics>ΔTmax</semantics> and smoke spread in tunnels. When fire occurs inside the branch tunnel, the main tunnel airflow obstructs downstream smoke movement, leading to a higher <semantics>ΔTmax</semantics> and expanded smoke spread upstream of the branch tunnel. A prediction model for <semantics>ΔTmax</semantics> under cooperative ventilation in underground interconnected tunnels was established, accounting for variations in fire position and the HRR. Meanwhile, the temperature distribution upstream of the branch tunnel was studied, revealing that the HRR has minimal impact on it. When fire occurs outside of the branch tunnel, v2 significantly affects temperature attenuation within the branch tunnel. When fire occurs at the branch tunnel entrance or inside, v2 has less effect. Combining the ventilation scheme and the HRR, dimensionless temperature decay models for different fire locations were proposed. These findings offer valuable insights for smoke control in underground interconnected tunnels.